Occupational Class and Cancer Survival in Korean Men: Follow-Up Study of Nation-Wide Working Population - Lee, Hye-Eun (Int J Environ Res Public Health, 2020)
Background: We aimed to describe inequalities in site-specific cancer survival across different occupational classes in Korean men. Methods: Subjects included cancer diagnosed members of the national employment insurance program during 1995–2008. A total of 134,384 male cases were followed by linking their data to the Death registry until 2009. Occupational classes were categorized according to the Korean Standard Occupational Classification (KSOC). Hazard ratio adjusting age and diagnosed year were calculated for each occupation by cancer sites. Results: Men in service/sales and blue-collar occupations had lower survival of all cancer sites combined and esophagus, stomach, colorectal, liver, larynx, lung, prostate, thyroid cancer and non-Hodgkin’s lymphoma than men in professional and managerial positions. Cancer sites with good prognosis like prostate cancer showed wider gap across occupational class. Conclusions: Considerable inequalities in cancer survival were found by occupation among Korean men. Cancer control policy should more focus on lower socioeconomic occupational class.